Pengaruh Kualitas Pelayanan Dan Harga Terhadap Word Of Mouth, Melalui Kepuasan Orang Tua Sebagai Variable Intervening Pada Lembaga Kursus Gambar Funart Studio Di Kota Semarang - Fhery Catur Wibowo; Fathorrahman; Theresia Pradiani (Faculty of Economics and Business, Universitas Warmadewa, 2024)
This research aimed to analyze the influence of service quality and price on word of mouth, with customer satisfaction acting as the intervening variable, at FunArt Studio in Semarang. Data for this study were obtained through the distribution of questionnaires, resulting in a sample size of 68 respondents. The data were analyzed using path analysis and the Sobel test with SPSS 25.0. The findings of this study concluded that (1) service quality has a significant direct and indirect impact on word of mouth through customer satisfaction, (2) price has a significant direct and indirect impact on word of mouth through customer satisfaction, and (3) customer satisfaction has a significant impact on word of mouth..